The Effect of Low and Moderate Intensity Aerobic Exercises on Self-Concept in Older Adults - Ahmad Ali Akbari Kamrani; Amir Shams; Behrooz Abdoli; Parvaneh Shamsipour Dehkordi (University of Social Welfare & Rehabilitation Sciences, 2015)
Objectives The purpose of present study was to investigate the effect of low and moderate intensity aerobic exercises on self-concept in older adults.  Methods & Materials The research method was quasi-experimental with pre-test and post-test design. The statistical sample included 45 volunteer elderly men with age mean of 58.88±2.70 years old that divided randomly in two experimental groups (aerobic exercise with low and moderate intensity) and one control group. First, all subjects were evaluated by a proficient doctor to confirm their physical and mental health. Also, the maximum heart rate (HR) of subjects was obtained by subtracting one's age from 220. Furthermore, based on aerobic exercise type (40-50% Max HR for low intensity group and 60-70% Max HR for moderate intensity group) the target maximum HR was calculated for each subject. The exercise protocol consisted of 8 weeks aerobic exercises (2 sessions in per week) based on Rockport one-mile walking/running test. Exercise intensity was evaluated and controlled using specific chest belts. All subjects in per-test and post-test stages were completed the Tennessee Self-concept Scale 2 (TSCS2).  Results In pre-test stage, the results showed that there were no significant differences between control and experimental groups in self-concept (P>0.05). On the other hand, results in post-test stage showed that there were significant differences between control and experimental groups in this variable (P<0.05). Also, the Tukey Post Hoc showed that the moderate intensity group scores in self-concept was better than other groups (P<0.05). Finally, the low intensity group scores were better than control group (P<0.05).  Conclusion Aerobic exercises with moderate intensity (60-70% max HR) have a positive and significant effect on self-concept. Based on these findings, aerobic exercises with moderate intensity is recommended as a useful method for improving this personality trait among older adults.